Analisa Hubungan Mesin-Mesin Produksi Terhadap Biaya Ekonomi Pada PT. Dok Tawiri - Ambon - O. Metekohy (ARIKA, 2012)
Every marine and naval architectur indusrties need to produce a ship at a more low cost to maintain themselve as a strong, independent and competitive company. This can be realized by organizing the use of production machines to minimize the total production cost. The research is conducted to detect the use level of production machines from economics view by using break even analysis method. Results show the level of company expendeture at Rp. 12.796.909.00, income at Rp. 13.149.400.00 and profit at Rp. 325.491.